A rare testicular tumor with elevated alkaline phosphatase - Mohammadreza Khosravifarsani; Mohammad Bahadoram; Seyed Mohamad Kazem Nourbakhsh; Roham Nikkhah; Mohammad Davoodi (Society of Diabetic Nephropathy Prevention, 2018)
Background: The majority of Leydig cell tumors (LCTs) are found in males, usually when they have 5-10 years of age. Children typically present with precocious puberty due to excessive testosterone secreted by the tumor, one-third of female patients present a recent history of progressive masculinization. Alkaline phosphatase is normally at low levels. Case Presentation: A 30-year-old male referred to the hospital with a complaint of fever, chills, nausea and weight loss, and history of diabetes mellitus type 1. In the physical examination of testis, no abnormal findings were revealed. Scrotal ultrasonography demonstrated a small (7.5 ×4.8 mm) mass which seemed to be very vascular and suggestive of neoplastic lesion. Echogenicity of the head of the right epididymis was heterogeneous and the small cyst of about 4.5 mm was present on it. Left testis had normal size and no space occupying lesion in it. The hormonal test revealed high levels of alkaline phosphatase, ferritin, FSH and LH, normal level of testosterone, LDH, β-HCG and α-feto-protein. Immunohistochemistry results revealed negative CD30, alpha-fetoprotein and CK results, but calretinin, vimentin and S-100 were positive in tumor cells. Conclusions: LCTs are rare testicular tumors arising from male gonadal interstitium and very rare in adulthood. Because this tumor consists of immature embryonic tissues it can be accompanied by an elevation in alkaline phosphatase level.